The verb in Arte de la lengua española castellana, by Gonzalo Correas - Hernando Cuadrado, Luis Alberto (Revista de Filología Románica, 2012)
The general frame of Gonzalo Correas’ doctrine on the verb is in the line of Dionysus Thrax and the Latin grammarians. In the Spanish grammatical tradition, Nebrija is the author who influences more on Correas. Nevertheless, there is a difference of focus between them because Nebrija explains the phenomena in a brief way and Correas does it more detailedly. On the other hand, the Extremaduran humanist pays attention to the vulgar and dialectal forms and sometimes he indicates if the phenomena are in force or not in the epoch and the social level in which are used.
Keywords: Gonzalo Correas; verb; grammatical tradition; linguistic varieties